Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1360-0443.2003.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

The cigar as a drug delivery device: youth use of blunts

Abstract: The use of blunts as a drug delivery device is a serious problem. Efforts to address it will require the cooperation of the tobacco control and substance abuse prevention systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…Our findings also corroborated prior research that found youths tend not to define smoking blunts as cigar use (Yerger et al, 2001;Soldz et al, 2003). These findings provide further evidence that the increase in youthful cigar use during the 1990s was probably not due to youths reporting their smoking blunts as cigar use.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings also corroborated prior research that found youths tend not to define smoking blunts as cigar use (Yerger et al, 2001;Soldz et al, 2003). These findings provide further evidence that the increase in youthful cigar use during the 1990s was probably not due to youths reporting their smoking blunts as cigar use.…”
Section: Discussionsupporting
confidence: 82%
“…One participant said, "When I hear cigar, I think old people with them big ones." In 2001, Soldz, Huyser, and Dorsey (2003) explicitly tested whether 5,016 Massachusetts students in grades 7-12 defined blunt smoking as cigar use. They were interested in determining whether increases in youthful cigar use during the 1990s might have been caused by blunt smokers reporting their behavior as cigar smoking.…”
Section: The Role Of Blunt Smoking In the Latest Marijuana Eramentioning
confidence: 99%
“…Black, Multiracial, and LGB youth were significantly more likely report "other" as their usual mode of consumption, as were those reporting early marijuana use (i.e., use before age 13), frequent marijuana use (i.e., used >20 times in the past 30 days), and cigarette smoking. Because blunt use (i.e., smoking marijuana using a hollowed-out cigar) is more common among Blacks, those who report cigarette smoking, and those with a cannabis use disorder (Fairman, 2015;Golub, 2006;Soldz et al, 2003), some youth reporting "other" as their usual mode of consumption may have been referring to blunt use (i.e., they may consider blunt use as distinct from smoking marijuana). Future studies could provide clarity about other modes of use by inviting participants to specify the modes they are referring to.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess the relationship between the use of blunts, marijuana and cigars given the current state of question construction in most of the national drug and tobacco surveys, which do not clearly distinguish between cigars for cigars and cigars for blunts nor clearly include blunt use as a form of marijuana consumption. Some researchers have questioned whether youths might be reporting blunt use as cigar use [6], thus overrepresenting their use of cigars as cigars. Conversely, since blunts are a means of smoking marijuana, youths may be reporting their blunt use within their use of marijuana and thus underrepresenting their use of cigars for blunts.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of adolescent use of blunts and cigars, Soldz et al [6] compared survey data on use of cigars, including possibly blunts, with data on use of cigars specifically excluding blunts, and found that while use of cigars and blunts were related, cigar smoking was distinct from blunt smoking. Similarly, Ream et al [8] were able to distinguish characteristics of respondents who tended to smoke marijuana in joints (rolled in cigarette papers) from those who tended to smoke it in blunts.…”
Section: Introductionmentioning
confidence: 99%